PENGARUH LAYANAN BIMBINGAN KELOMPOK TERHADAP ETIKA BERKOMUNIKASI SISWA KELAS XI MA PP DAARUT THAALIBIIN KOTA DATAR T.P. 2018/2019 - Tumiyem Tumiyem; Samsiah Samsiah (Al-Irsyad: Jurnal Pendidikan dan Konseling, 2018)
This study aims to determine the effect of group guidance services on communication ethics of class XI MA PP Daarut Thaalibiin Kota Datar 2018/2019 academic year. The method used in this study is a pre-experimental method with one group pretest and posttest design experimental design. The population in this study were 30 students. The sample of this study was 30 students. Data retrieval is done by questionnaire instrument. The results of this study are that there is the influence of group guidance services on the communication ethics of class XI MA PP Daarut Thaalibiin Kota Datar in the 2018/2019 academic year.Keywords: Group Guidance Services, Communicating Ethics